GPS-based Track and Trace Smart Farming Application to Increase Domestic Market Share for Melon Farmers - Ananda Faridhatul Ulva; Fadhliani Fadhliani; Novianda Novianda (Pengabdian: Jurnal Abdimas, 2025)
Millennial farmers are defined as farmers aged 18-55 years old. In North Aceh Regency, the number of millennial farmers, particularly in Lhoksukon Village, has increased rapidly in 2023. These millennial farmers face challenges in marketing their products and monitoring their agricultural activities remotely and in real-time, such as water management and crop irrigation. The aim of this activity is to increase farmers' interest in agriculture in order to make millennial farmers more advanced and independent and to achieve food security in Lancang Barat Village, Dewantara Sub-district, North Aceh. The partners in this activity are the Geuthena farmer group in Lancang Barat Village, Dewantara Sub-district, North Aceh, consisting of 10 farmers. The data collection techniques used in this community service activity were observation, interviews, and questionnaires to identify the problems that occur. The methods used in this activity were workshops, training, counseling, and mentoring for farmers for 4 months in the use of ASSA (Smart Shopp Agriculture Application) technology for distribution channels in the e-marketplace system. The results of this activity were an increase in understanding of the use of digital technology, enabling farmers to reach a wider market and allowing them to sell their products directly to consumers. Some brief findings from this activity included a significant 80% increase in the use of digital technology with the ASSA application among the Geuthena farmer group, a 30% increase in product sales in the first three months, and faster product delivery times. This activity has successfully improved farmers' digital skills and optimised distribution channels, which can significantly contribute to food security.